Abd al-Rauf's Contributions to Quranic Exegesis: Historical Context, Methodology, and Malay Translation - Zainuddin, Anayya Syadza; Kamaruddin, Kasimah Binti; Zainuddin, Zainuddin (SINTHOP: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2024)
This study explores Abd al-Rauf's influence within the geographic and historical milieu of Aceh, focusing on his contributions during the reign of four sultanas and his role as Qadi Malik al-Adil. It underscores his historical approach to Quranic exegesis and efforts to make Quranic teachings accessible to Malay-speaking audiences. Using a systematic literature review, the study analyzes 21 key documents on Abd al-Rauf's contributions. Documents were selected based on relevance to three themes: geographic and historical context, tafsir methodology, and Quranic translation. Findings reveal that 43% of the literature highlights Abd al-Rauf's historical influence, 19% discusses his tafsir methodology, especially in Turjuman al-Mustafid, and 38% examines his translation of the Quran into Malay using the Jawi script. The study concludes that Abd al-Rauf's contributions have significantly enriched the Islamic intellectual tradition in Southeast Asia, enhancing the region's scholarly and cultural heritage and providing a foundation for ongoing research into Quranic exegesis and Islamic teachings in the Malay world.